p75NTR antibody-conjugated microspheres: an approach to guided tissue regeneration by selective recruitment of endogenous periodontal ligament cells - Zou, Xuqiang; Xie, Bo; Peng, Xuelian; Lu, Mingjie; Xu, Dan; Yuan, Hongyan; Zhang, Yixin; Wang, Di; Zhao, Manzhu; Liu, Rui; Wen, Xiujie (Frontiers in Bioengineering and Biotechnology, 2024)
Repairing defects in alveolar bone is essential for regenerating periodontal tissue, but it is a formidable challenge. One promising therapeutic approach involves using a strategy that specifically recruits periodontal ligament cells (PDLCs) with high regenerative potential to achieve in situ regeneration of alveolar bone. In this study, we have created a new type of microsphere conjugated with an antibody to target p75 neurotrophin receptor (p75NTR), which is made of nano-hydroxyapatite (nHA) and chitosan (CS). The goal of this design is to attract p75NTR + hPDLCs selectively and promote osteogenesis. In vitro experiments demonstrated that the antibody-conjugated microspheres attracted significantly more PDLCs compared to non-conjugated microspheres. Incorporating nHA not only enhances cell adhesion and proliferation on the surface of the microsphere but also augments its osteoinductive properties. Microspheres effectively recruited p75NTR + cells at bone defect sites in SD rats, as observed through immunofluorescent staining of p75NTR antibodies. This p75NTR antibody-conjugated nHA/CS microsphere presents a promising approach for selectively recruiting cells and repairing bone defects.